Los grupos políticos tebanos en el periodo de la hegemonía (371-362 a. C.) - Pascual, José (Estudios humanísticos. Geografía, historia y arte, 1991)
This paper tries to establish the differents the bans political groups between the years 371-362 B.C.: the Epaminondas and Pelópidas group (warlike party), the Meneclidas dique or «peace party», the filolaconical oligarchs exiled and the possibility, only the possibility, of a radical democratic faction.